Linking the Role of Promotion of Access to Digital Facilities, Social Media and Digital Literacy on Marketing Performance - Praditya, Rayyan Aqila (UJoST- Universal Journal of Science and Technology, 2024)
This research attempts to fill the gap in the differences in the relationship between promotion and marketing performance. Considering that currently social media has become so important, this research focuses on promotion via social media. Social media promotions have different influences on marketing performance, where these differences depend on the digital access that business actors have. Therefore, digital access is positioned as a moderator between social media promotion and marketing performance. Digital access is used as moderation because it can increase or decrease marketing performance. This research reviews the variables of social media promotion and digital literacy with access to digital facilities as a moderation of marketing performance. This research method is qualitative research, data comes from 456 respondents with data collection methods using questionnaires. The method for data analysis uses a structural model processed with smartPLS. 3.0. The result is that social media promotion has an effect on marketing performance, digital literacy has an effect on marketing performance, access to digital facilities is not able to moderate social media promotion and digital literacy has an effect on marketing performance.